154 Patients receiving standard pacemaker generator replacements frequently have impaired left ventricular function and exercise intolerance, related to the percentage of right ventricular pacing. (9th June 2011) - Begg, G A; Gierula, J; Waldron, Z L; Witte, K K
Abstract : Background: Right ventricular (RV) pacing is an accepted treatment for symptomatic bradycardia. However, long-term RV pacing is increasingly recognised to be detrimental to left ventricular (LV) systolic function. We wanted to establish the prevalence, associated features and predictors of LV systolic dysfunction (LVSD) and outcome in a contemporary group of patients with long–term RV pacemakers. Methods: We prospectively recruited consecutive patients listed for PGR between 2008 and 2010 at Leeds General Infirmary. We performed echocardiography, exercise testing and recorded indications for pacing, pacing variables and duration of pacing, co-morbidities, current medication and renal function. Results: Of 399 PGR procedures 342 subjects (86%), 184 men, attended. Non-attendees had similar pacing variables and were of similar age as attendees. Mean age (SE) was 76 (1), and mean duration of pacing was 10 (0.3) years. Comorbidites were common: diabetes mellitus in 11%, previous myocardial infarction in 15%, previous cardiac surgery in 26% and atrial fibrillation (AF) in 26%. Medical therapy included β-blockers in 60% and ACE inhibitors in 70%. Dual chamber devices were implanted in 77% (45% of all patients had rate responsive (RR) pacing programmed). Mean percentage of ventricular pacing (%VP) was 61 (2)%. Mean left ventricular ejection fraction (LVEF) was 49 (1)%, (44% had an LVEF <50%). Mean peak oxygen uptake (pVo2 ) (in 107 subjects) was 17 (1) ml/kg/min and mean creatinine was 108 (3) μmol/l. There was an inverse relationship between LVEF and %VP (0.42; p<0.0001), and years since first implanted (p=0.09) but there was no effect on LVEF of age, the presence of AF and the pacing mode. In single chamber devices, RR pacing was associated with higher %VP (p=0.01), and a trend to worse LVEF (p=0.09). These differences were not seen in RR programmed dual chamber devices. There was a negative relationship between pVo2 and %VP (r=0.21; p<0.03). Even with a short follow-up period of 16 (0.5) months, 23 (7%) patients are dead. Patients dead at the censor date were older at the time of the assessment (p<0.005), had a higher %VP (p<0.03) and worse renal function (p<0.001), but did not have significantly worse LVEF or pVo2 . The presence of a single chamber device was associated with a poorer outcome (p<0.002) despite patients with a single chamber device being of similar age as those with a dual chamber device. Conclusions: Patients receiving standard pacemaker generator replacements frequently have cardiovascular comorbidities, left ventricular dysfunction and impaired pVo2 and suffer a high mortality rate. In an unselected population of patients with pacemakers, we have established that the amount of RV pacing is related not only to important surrogate measures of outcome such as exercise tolerance and LVEF but also mortality. Whether an aggressive policy of limiting RV pacing in patients at risk reduces mortality is unknown.